The glacial geomorphology of upper Godthåbsfjord (Nuup Kangerlua) in south-west Greenland - Pearce, Danielle; Mair, Douglas; Rea, Brice; Lea, James; Schofield, J. Edward; Kamenos, Nicholas; Schoenrock, Kathryn (Journal of Maps, 2018)
© 2018 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group on behalf of Journal of Maps. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/4.0/), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited. The Greenland Ice Sheet (GrIS) is known to have experienced widespread retreat over the last century. Information on outlet glacier dynamics, prior to this, are limited due to both a lack of observations and a paucity of mapped or mappable deglacial evidence which restricts our understanding of centennial to millennial timescale dynamics of the GrIS. Here we present glacial geomorphological mapping, for upper Godthåbsfjord, covering 5800 km 2 at a scale of 1:92,000, using a combination of ASTER GDEM V2, a medium-resolution DEM (error < 10 m horizontal and < 6 m vertical accuracy), panchromatic orthophotographs and ground truthing. This work provides a detailed geomorphological assessment for the area, compiled as a single map, comprising of moraines, meltwater channels, streamlined bedrock, sediment lineations, ice-dammed lakes, trimlines, terraces, gullied sediment and marine limits. Whilst some of the landforms have been previously identified, the new information presented here improves our understanding of ice margin behaviour and can be used for future numerical modelling and landform dating programmes. Data also form the basis for palaeoglaciological reconstructions and contribute towards understanding of the centennial to millennial timescale record of this sector of the GrIS. Peer reviewed